Determinants of Integrated Reporting Quality of Financial Firms - Yashini Pillai; Keshav Seetah (The Indonesian Journal of Accounting Research, 2022)
Despite existing studies on the determinants of integrated reporting quality, such studies are rare in the financial sector. The aim of this study is to investigate the determinants of integrated reporting quality of financial firms. More specifically, the influence of firm size, firm age, profitability, auditor size, length of integrated report, institutional quality and economic development, on integrated reporting quality. The data for this study was obtained from a sample of 18 financial firms across 18 countries for the period of 2013 to 2019 with a total of 106 firm year observations. Using content analysis, an integrated reporting index was developed for the purpose of this research which was then used to measure integrated reporting quality for each firm year. The research findings reveal that integrated reporting quality of financial firms is positively influenced by firm age, length of integrated report and institutional quality. However, this study reveals that firm size, profitability, leverage, auditor size and economic development have no significant influence on the integrated reporting quality of financial firms. This study contributes to the scarce literature on the determinants of integrated reporting quality in the financial sector.